ANALYSIS OF THE ABILITY TO PUSH HOVERCRAFT VEHICLES TO SUPPORT ARMY SWAMP OPERATIONS - Endia Muhamat Nur; Mohammad Ma'ruf; Agus Mulyono (TRANSMISI, 2019)
A hovercraft is an amphibious vehicle that works on an air cushion, capable of traveling on land and water terrains. This vehicle is driven by two systems, namely the lifting system and the propulsion system. The propulsion system functions to produce a thrust that will drive the hovercraft vehicle forward. The thrust is influenced by engine speed, transmission, shaft rotation, fan design, air flow speed, flow rate mass, and air discharge. This research method is carried out by varying the engine speed, starting from 1000rpm, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm, 2200rpm rotation. The results of the research and data processing showed that the higher the rotation of the shaft, the greater the thrust generated. Where at a minimum engine speed of 1000 rpm, the shaft rotation of 436 rpm produces a thrust of 11.794 Newton. Whereas at the maximum 2200 rpm engine speed, the 1060 rpm shaft rotation produces a thrust of 87.664 Newton.